Employability skills, job performance and promotability of employees working in SMEs Malaysia - Juhdi, Nurita; Hashim, Junaidah (2013)
The study aimed to examine the relationships between employability skills of university graduates and three variables namely self-directed learning readiness (SDLR), job performance and promotability. All the respondents who participated in the study were employers in small and medium enterprises in Malaysia. They must qualify these criteria - human resource managers (or any managers who are in the capacity to recruit and hire people) of a company in small and medium enterprises (SMEs) and they have been hiring university graduates. In total, there were 104 respondents. The respondents were required to rate the university graduates they have hired for the past 2 years. The study results managed to indicate that all the employability skills (except for ICT skills) were significantly related to each other. This implies that all these skills are complementing each other and university graduates have to have all these skills in them especially if they wish to work in SMEs. It was also revealed that among all the five SDLR dimensions, only joy for learning that was unrelated to any of the employability skills. The case was different from the other dimensions especially independent learner and initiative to learn that were significantly related to many employability skills. Unlike SDLR, it was found that most employability skills were significantly related to job performance and promotability (except for ICT and oral/written communication skills) It is also important to note that the most preferred CGPA level of university graduates hired by SMEs are between 3.0 to 3.4.